PEMAHAMAN KONSEP MATEMATIS SISWA DENGAN STRATEGI PEMBELAJARAN GROUP TO GRUOP EXCHANGE BERPENDEKATAN KONTEKSTUAL - Rosmaiyadi Rosmaiyadi; Mariyam Mariyam; Juliyanti Juliyanti (JPPM (Jurnal Penelitian dan Pembelajaran Matematika), 2018)
ABSTRACTThis study aims to determine differences in the increase in the ability of understanding mathematical concepts among students were given group to group exchange learning strategy with contextual approach with students who are given direct instructional model, determine students' individually and classical  learning completeness and know the learning activities of students. This research uses Quasi Experimental design with Nonequivalent Control Group Design. The population in this research is all class VIII SMP 12 Singkawang consisting of four classes totaling 84 students. The sample was taken by by purposive sampling technique. The sample consists of two classes, namely class VIII B as the experimental class were 21 students and class VIII C as the control class as many as 21 students. The results showed that there were differences increased ability of understanding mathematical concepts among students given group to group exchange learning strategy with contextual approach with students who are given direct learning model, the students achieved complete learning individually or classically and the students' learning activities were quite active. Keywords:  Mathemactical Understanding, Group to Group Exchange Strategy, Contextual Approach